Analisis Kepuasan Pelanggan Terhadap Kendaran Motor Yamaha - Rico Sandi Aji; Samsul Bahri; Syamsul Hidayat (Institut Nalanda, 2024)
Motorbike factories have developed very rapidly throughout the world, one of which is in Indonesia. Customer satisfaction is a sum of the attitudes shown by customers or consumers regarding the use or acquisition of a product and providing experience in using it (Sumarwan, 2017: 387) .The method used in this research is a quantitative or statistical method. The population in this research is all the people of Serang City who have or often buy Yamaha products. The number of respondents that has been determined is 101 respondents. Based on the results of research on 101 respondents and discussion regarding the level of consumer satisfaction with Yamaha brand motorbikes, it can be concluded that Yamaha motorbike consumers in Serang City are in the quite satisfied category when using Yamaha products.